Hemorrhagic Stroke in Dengue; A Rare Sole Presentation - Biswas, Dr. Tapan (International Journal of Innovative Research in Medical Science, 2017)
Dengue fever is a major public health problem in tropical countries. Clinical manifestations range from a nonspecific viral syndrome to a severe fatal hemorrhagic disease. Hemorrhagic stroke as the sole presentation in dengue is very rare. We report one adult male who presented with high fever, generalized bodyache with alter sensorim and left sided hemiplegia. Dengue was suspected because of thrombocytopenia and epidemic of dengue in West Bengal. In dengue epidemic area, dengue should be considered as probable eitiological causes of hemorrhagic CVA. We have confirmed these case by NS1Ag, Dengue IgM antibody, IgG antibody and Low platelate count in his blood.